Refugee law - Baglay, Sasha (Irwin Law, 2017)
Refugee Law is a concise account of Canadian refugee law, policy, and procedure. It presents refugee law as an independent system, yet one that is open to and influenced by other branches of domestic law, international law, the practices of other jurisdictions, and the general global trends in forced migration. The book examines the historic and contemporary context of refugee law, formal law, and government policy, and the domestic and international principles of refugee protection. The authors seek to provide a solid foundation from which to judge the merits and weaknesses of the existing system, allowing the reader to engage with the ongoing debate, both academic and popular, about the Canadian refugee system.